Improving Color Fastness of Natural Dyes from Siwalan Fruit Skin (Borassus flabellifer L.) on Cotton and Shantung Fabrics Using Various Fixing Agents - Husnun Hanifah; Sugiyem Sugiyem (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This study aims to determine the effect of using alum powder, iron sulfate (tunjung) solution, and pure lime (quicklime) as fixing agents on the color fastness of dyeing using Siwalan fruit peel extract on primissima cotton and shantung fabric in terms of washing and ironing. The research design was a 3×2 factorial experiment using natural dyes from Siwalan fruit peel obtained from traders on Jalan Imogiri Timur, Yogyakarta. The samples consisted of primissima cotton and shantung fabric, while the fixing agents used included quicklime, alum powder, and iron sulfate solution. Data were collected through color fastness tests against washing and heat from ironing conducted by the UII Textile Manufacturing and Testing Laboratory. Results were analyzed using the Kruskal-Wallis test. The findings demonstrated that using different fixing agents significantly affected color fastness. Specifically, alum powder produced superior color fastness to washing on primissima cotton fabric (average score of 4.0), while all three fixing agents showed equivalent performance on shantung fabric (average score of 4.0). For heat resistance during ironing, alum powder and iron sulfate solution achieved the highest scores (4.5 on average) on both fabric types, representing a 12.5% improvement over the quicklime treatment (4.0). These results indicate that the selection of fixing agents is crucial for optimizing the color fastness properties of natural dyes from Siwalan fruit peel.